Title: pancreatic‐type mixed acinar neuroendocrine carcinoma of the stomach: a case report and review of the literature - Yuka Ooe; Kishichiro Watanabe; Isaya Hashimoto; Satoshi Takenaka; Toshihiko Ojima; Seiichi Yamamoto; Hisatake Fujii (BMC, 2021)
Abstract Background The majority of gastrointestinal tumors are adenocarcinomas. Rarely, there are other types of tumors, such as acinar cell carcinoma, and these are often called pancreatic-type acinar cell carcinomas. Among these tumors, some are differentiated into neuroendocrine components. A few of them are MiNENs. Case presentation The patient was an 80-year-old male who was referred to our hospital for treatment of a pedunculated gastric tumor. It was 5 cm in diameter and detected in the upper gastric body with upper GI endoscopy conducted to investigate anemia. In the biopsy, although hyperplasia of gastric gland cells was noted, no tumor cells were found. Retrospectively, the diagnosis was misdiagnosed. An operation was arranged because bleeding from the tumor was suspected as a cause of anemia and because surgical resection was considered to be desirable for accurate diagnosis. Hence, laparoscopic and endoscopic cooperative surgery was performed. In the pathological examination, several types of epithelial cells that proliferated in the area between the mucosa and deep inside the submucosa were observed. These consisted of acinar-glandular/trabecular patterns and solid. A diagnosis of pancreatic-type acinar cell carcinoma of the stomach with NET G2 and G3 was made based on characteristic cellular findings and the results of immunostaining tests. Each of them consisted of more than 30% of the lesion; a diagnosis of pancreatic-type mixed acinar neuroendocrine carcinoma (pancreatic-type MiNEN) of the stomach or a type of gastric MiNEN was obtained. Anemia was resolved after the operation, and the patient was discharged from the hospital without perioperative complications. Conclusions Pancreatic-type ACC of the stomach that is differentiated into neuroendocrine tumors is very rare. Hence, we report this case along with a literature review.